Unilateral Tubarial Oncocytic Papillary Cystadenoma Presenting with Epistaxis - Nurul Syuhadah Hasny; Fatihatul Munirah Amiruddin; Faezahtul Arbaeyah Hussain; Baharudin Abdullah (Medeniyet Medical Journal)
Oncocytic papillary cystadenoma (OPC) is a relatively rare benign tumor of the salivary glands, frequently seen in minor salivary glands, and occasionally in major salivary glands, such as the parotid gland. Patients only become symptomatic upon progression of the swelling, causing obstructive symptoms depending on its location. To our knowledge, there are no reports of presentation with bleeding tumor. Herein, we report a case of an OPC of the right torus tubarius in a 54-year-old man who presented with recurrent epistaxis.